2015
DOI: 10.1002/jms.3530
|View full text |Cite
|
Sign up to set email alerts
|

Redox activity and multiple copper(I) coordination of 2His–2Cys oligopeptide

Abstract: Copper binding motifs with their molecular mechanisms of selective copper(I) recognition are essential molecules for acquiring copper ions, trafficking copper to specific locations and controlling the potentially damaging redox activities of copper in biochemical processes. The redox activity and multiple Cu(I) binding of an analog methanobactin peptide-2 (amb2) with the sequence acetyl-His1-Cys2-Tyr3-Pro4-His5-Cys6 was investigated using ion mobility-mass spectrometry (IM-MS) and UV-Vis spectrophotometry anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…[15] These results strengthen our analogy between "organic" and Lewis acid electrophiles and suggest that in addition to being useful probes of NC topography,the Au-based agents could provide arich source of targeted anti-HIV agents based on athiolate modification strategy. The observation of aurated a 5 showed that Cys 5 is ag old-binding site while the aurated y 9 is indicative of auration at either His 20 or His 24 .T he observation of aurated y 21 ,y [23][24][25] ,and y 27 is also consistent with the binding at His 20 /His 24 and Cys 5 (Figure 4c). The observation of aurated a 5 showed that Cys 5 is ag old-binding site while the aurated y 9 is indicative of auration at either His 20 or His 24 .T he observation of aurated y 21 ,y [23][24][25] ,and y 27 is also consistent with the binding at His 20 /His 24 and Cys 5 (Figure 4c).…”
Section: Zuschriftensupporting
confidence: 62%
See 2 more Smart Citations
“…[15] These results strengthen our analogy between "organic" and Lewis acid electrophiles and suggest that in addition to being useful probes of NC topography,the Au-based agents could provide arich source of targeted anti-HIV agents based on athiolate modification strategy. The observation of aurated a 5 showed that Cys 5 is ag old-binding site while the aurated y 9 is indicative of auration at either His 20 or His 24 .T he observation of aurated y 21 ,y [23][24][25] ,and y 27 is also consistent with the binding at His 20 /His 24 and Cys 5 (Figure 4c). The observation of aurated a 5 showed that Cys 5 is ag old-binding site while the aurated y 9 is indicative of auration at either His 20 or His 24 .T he observation of aurated y 21 ,y [23][24][25] ,and y 27 is also consistent with the binding at His 20 /His 24 and Cys 5 (Figure 4c).…”
Section: Zuschriftensupporting
confidence: 62%
“…[5,14] For{ AuF} derived from Sp1-F3, only one conformation was observed (for its MS/MS spectrum, see Figure 4c). The observation of aurated a 5 showed that Cys 5 is ag old-binding site while the aurated y 9 is indicative of auration at either His 20 or His 24 .T he observation of aurated y 21 ,y [23][24][25] ,and y 27 is also consistent with the binding at His 20 /His 24 and Cys 5 (Figure 4c). Thei dentified gold-binding fragments from the MS/MS spectrum are shown in Table S3.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Our previous IM‐MS studies of metal binding have shown behavior that is closely correlated to that of the solution phase, because the covalent interactions between the metal ion and peptide are robust enough to be conserved during electrospray ionization (ESI). Previous studies included the methanobactin from Methylosinus trichosporium (mb‐OB3b) and analog methanobactin (amb) oligopeptides which replaced the two enethiol oxazolone binding sites of mb‐OB3b with the 2His‐2Cys binding motif . From solution‐phase chemistry, the amb 5A‐F (Figure A ‐ F ) would be expected to exhibit an overall charge based on the protonation state of their acidic and basic sites, ie, the C‐terminus carboxyl group (p K a ≈ 3), His (p K a ≈ 6.0), Cys (p K a ≈ 8.3), and Tyr (p K a ≈11.0) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies included the methanobactin 3,4 from Methylosinus trichosporium (mb-OB3b) and analog methanobactin (amb) oligopeptides which replaced the two enethiol oxazolone binding sites of mb-OB3b with the 2His-2Cys binding motif. 1,[5][6][7] From solution-phase chemistry, the amb 5A-F ( Figure 1A-1F) would be expected to exhibit an overall charge based on the protonation state of their acidic and basic sites, ie, the Cterminus carboxyl group (pKa ≈ 3), His (pKa ≈ 6.0), Cys (pKa ≈ 8.3),…”
Section: Introductionmentioning
confidence: 99%